Analysis of Factors Influencing Literacy of Halal Tourism in West Java, Indonesia - HS, Sufyati; Wiryanto, Fadhli Suko; Resti, Anggi Angga; Hadi, Prasetyo (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
The aim of this research is to analyze the influence of perceptions and attitudes on halal tourism literacy which is mediated by interest in visiting halal tourist destinations. This research uses a quantitative approach design with the Partial Least Square/PLS-SEM method, namely analysis used to develop or predict an existing theory. Data collection was carried out by distributing questionnaires online and offline to visitors to tourist destinations in the Depok City Area as a satellite city of Indonesia. The population in this study were all visitors to halal tourist destinations under the guidance of the Depok City government, with samples selected using purposive sampling techniques. The number of research samples used was 101 people. The research results show that people's perceptions, attitudes and interest in halal tourism have a positive influence on halal tourism literacy. People's perceptions and attitudes towards halal tourism can each have a direct or indirect influence on halal tourism literacy and interest in halal tourism.